Developing Logistics Services in the Rice Export Supply Chain in the Mekong Delta - Van, Hoang Thi (Archives of Business Research, 2025)
The Mekong Delta is Vietnam’s largest rice granary, contributing to making Vietnam one of the leading countries in rice production and export. To exploit and promote the full potential of the agricultural economy of this region, Vietnam faces the challenge of limited logistics, especially logistics services for export. This article aims to assess the current status of logistics services in the rice export supply chain in the Mekong Delta. At the same time, propose some solutions to develop logistics services in the rice export supply chain of this region.